-3(p-2)=12

Simple and best practice solution for -3(p-2)=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(p-2)=12 equation:


Simplifying
-3(p + -2) = 12

Reorder the terms:
-3(-2 + p) = 12
(-2 * -3 + p * -3) = 12
(6 + -3p) = 12

Solving
6 + -3p = 12

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -3p = 12 + -6

Combine like terms: 6 + -6 = 0
0 + -3p = 12 + -6
-3p = 12 + -6

Combine like terms: 12 + -6 = 6
-3p = 6

Divide each side by '-3'.
p = -2

Simplifying
p = -2

See similar equations:

| 50.24=2(3.14)r | | 5c-6=11 | | 3x+8=x-13 | | 50.24=2(314)r | | 6x^2+x-51=0 | | 10+2(z-5)=-5z+1 | | 7x+6.95=74.15 | | 7(4x-9)-13=-87 | | 6(x-1)=5 | | 2.3-5x=31-5x | | 8y^4-24y^3+18y^2= | | 99-9k=9k-27 | | 4x-3y=28 | | 14z^2-3=21z-7 | | 12+120037= | | 2x+1=2x-10 | | 4c-12=6c | | 14z^2-3=21z+7 | | x^5-36x=0 | | 6=-(3x+6) | | -8x+2x^2=0 | | 113=2l+2(28.5) | | -(x-9)=-4 | | 18-4q=-6 | | 16x^2-16x+7=0 | | 256x^4-81y^4=0 | | 30-4x=40-8x | | 8k-3=-9-6k | | 125x^3-216y^3= | | =2z^2+7z-4 | | 5n+3=3(1-2n) | | 5(x-4)=3(x+4) |

Equations solver categories